Question
upstudy study bank question image url

Suppose that the functions \( f \) and \( g \) are defined as follows. \[ \begin{array}{l} f(x)=3 x+5 \\ g(x)=\sqrt{5 x-3} \end{array} \] Find \( f \cdot g \) and \( f-g \). Then, give their domains using interval not \[ (f \cdot g)(x)= \] Domain of \( f \cdot g \) : \( \square \) \[ (f-g)(x)= \] \( \square \) Domain of \( f-g \) : \( \square \)

Ask by Rose Kirk. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ (f \cdot g)(x) = 3x\sqrt{5x - 3} + 5\sqrt{5x - 3} \] Domain of \( f \cdot g \): \(\left[\frac{3}{5}, \infty\right)\) \[ (f - g)(x) = 3x + 5 - \sqrt{5x - 3} \] Domain of \( f - g \): \(\left[\frac{3}{5}, \infty\right)\)

Solution

Simplify the expression by following steps: - step0: Remove the parentheses: \(\left(3x+5\right)-\sqrt{5x-3}\) - step1: Remove the parentheses: \(3x+5-\sqrt{5x-3}\) Expand the expression \( (3x + 5) * \sqrt(5x - 3) \) Simplify the expression by following steps: - step0: Distribute \(\sqrt{5x-3}\): \(\left(3x+5\right)\sqrt{5x-3}\) - step1: Distribute \(\sqrt{5x-3}:\) \(3x\sqrt{5x-3}+5\sqrt{5x-3}\) Solve the equation \( 5x-3 \geq 0 \). Solve the inequality by following steps: - step0: Solve for \(x\): \(5x-3\geq 0\) - step1: Move the constant to the right side: \(5x\geq 0+3\) - step2: Remove 0: \(5x\geq 3\) - step3: Divide both sides: \(\frac{5x}{5}\geq \frac{3}{5}\) - step4: Divide the numbers: \(x\geq \frac{3}{5}\) Solve the equation \( 5x-3 \geq 0 \). Solve the inequality by following steps: - step0: Solve for \(x\): \(5x-3\geq 0\) - step1: Move the constant to the right side: \(5x\geq 0+3\) - step2: Remove 0: \(5x\geq 3\) - step3: Divide both sides: \(\frac{5x}{5}\geq \frac{3}{5}\) - step4: Divide the numbers: \(x\geq \frac{3}{5}\) Let's solve the problem step by step. ### Step 1: Find \( f \cdot g \) The product of the functions \( f \) and \( g \) is given by: \[ (f \cdot g)(x) = f(x) \cdot g(x) = (3x + 5) \cdot \sqrt{5x - 3} \] Expanding this, we get: \[ (f \cdot g)(x) = 3x\sqrt{5x - 3} + 5\sqrt{5x - 3} \] ### Step 2: Find \( f - g \) The difference of the functions \( f \) and \( g \) is given by: \[ (f - g)(x) = f(x) - g(x) = (3x + 5) - \sqrt{5x - 3} \] This simplifies to: \[ (f - g)(x) = 3x + 5 - \sqrt{5x - 3} \] ### Step 3: Determine the domains #### Domain of \( f \cdot g \) The function \( g(x) = \sqrt{5x - 3} \) requires that the expression inside the square root is non-negative: \[ 5x - 3 \geq 0 \implies x \geq \frac{3}{5} \] Thus, the domain of \( f \cdot g \) is: \[ \text{Domain of } f \cdot g: \left[\frac{3}{5}, \infty\right) \] #### Domain of \( f - g \) The same condition applies for \( f - g \) since it also involves \( g(x) \): \[ \text{Domain of } f - g: \left[\frac{3}{5}, \infty\right) \] ### Final Answers \[ (f \cdot g)(x) = 3x\sqrt{5x - 3} + 5\sqrt{5x - 3} \] Domain of \( f \cdot g \): \(\left[\frac{3}{5}, \infty\right)\) \[ (f - g)(x) = 3x + 5 - \sqrt{5x - 3} \] Domain of \( f - g \): \(\left[\frac{3}{5}, \infty\right)\)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( f \cdot g \), we multiply the functions \( f \) and \( g \): \[ (f \cdot g)(x) = f(x) \cdot g(x) = (3x + 5) \cdot \sqrt{5x - 3}. \] Now, to determine the domain of \( f \cdot g \), we have to consider where both \( f(x) \) and \( g(x) \) are defined. The function \( g(x) = \sqrt{5x - 3} \) is defined when its argument is non-negative: \[ 5x - 3 \geq 0 \implies x \geq \frac{3}{5}. \] Thus, the domain of \( f \cdot g \) is \( [\frac{3}{5}, \infty) \). Next, we compute \( f - g \): \[ (f - g)(x) = f(x) - g(x) = (3x + 5) - \sqrt{5x - 3}. \] For the domain of \( f - g \), we again need to ensure \( g(x) \) is defined, so we still require: \[ 5x - 3 \geq 0 \implies x \geq \frac{3}{5}. \] Therefore, the domain of \( f - g \) is also \( [\frac{3}{5}, \infty) \). Now we can summarize the results: \[ (f \cdot g)(x) = (3x + 5) \cdot \sqrt{5x - 3} \] Domain of \( f \cdot g \): \( [\frac{3}{5}, \infty) \) \[ (f - g)(x) = (3x + 5) - \sqrt{5x - 3} \] Domain of \( f - g \): \( [\frac{3}{5}, \infty) \)

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy